Influence of Woven Fabric Construction on Seam Thread Slippage (Journal of Fiber Bioengineering and Informatics, 2016)
The aim of this paper is to investigate the effect of woven construction and tension of warp and weft inthe woven fabric on the seam slippage using a new approach with video analysis. The method includesmeasuring the surface of the resulting hole after subjecting the samples to seam slippage test, described instandard HRN EN ISO 13936-1:2008. The new method provides a more detailed and broader descriptionof seam damage caused by tensile stress. Testing was also conducted using the standard method bymeasuring the distance two adjacent threads. The results show that surface of resulting “hole” dependson the density of warp and weft and the weave of the fabric. The new approach enables a detailedoverview of the seam damage after tensile stress.